1998
DOI: 10.1128/jvi.72.5.4005-4014.1998
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Structure and Human Immunodeficiency Virus Type 1 cDNA Integration: Centromeric Alphoid Repeats Are a Disfavored Target

Abstract: Integration of retroviral cDNA into host chromosomal DNA is an essential and distinctive step in viral replication. Despite considerable study, the host determinants of sites for integration have not been fully clarified. To investigate integration site selection in vivo, we used two approaches. (i) We have analyzed the host sequences flanking 61 human immunodeficiency virus type 1 (HIV-1) integration sites made by experimental infection and compared them to a library of 104 control sequences. (ii) We have als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(56 citation statements)
references
References 62 publications
2
54
0
Order By: Relevance
“…In our protocol, transduced cells undergo ϳ8 subsequent cell divisions before final counting. Integration sites of the complemented D64VϩIN S vector in the chromosomal DNA of 293T cells were cloned using LTR-Alu PCR (43). Sequencing of 23 clones revealed that integration was preceded by specific 3Ј processing, thus confirming HIV-1 integrase-mediated integration (data not shown).…”
Section: Complementation Of In-defective Vector Particlesmentioning
confidence: 74%
“…In our protocol, transduced cells undergo ϳ8 subsequent cell divisions before final counting. Integration sites of the complemented D64VϩIN S vector in the chromosomal DNA of 293T cells were cloned using LTR-Alu PCR (43). Sequencing of 23 clones revealed that integration was preceded by specific 3Ј processing, thus confirming HIV-1 integrase-mediated integration (data not shown).…”
Section: Complementation Of In-defective Vector Particlesmentioning
confidence: 74%
“…The overall conformation of the PFV intasome structure changes little as the complex morphs from the SSC to the strand transfer complex and promotes IN 3Ј processing and strand transfer activities (16, 35,37,43,44). Although integration occurs largely throughout animal cell genomes (45,46), host DNA sequences that contort to fit the target DNA-binding interface within the CSC are preferred targets (37,44,(47)(48)(49) (for a detailed review, see Ref. 50).…”
Section: Intasome Structure and Functionmentioning
confidence: 99%
“…Although HIV-1 in large part integrates throughout the human genome (46), it does so in nonrandom fashion, on average favoring active genes that reside within relatively genedense regions of chromosomes (172). This targeting preference is largely dictated through specific interactions of two PIC-associated proteins, IN and capsid, with respective host factors LEDGF/p75 and cleavage and polyadenylation specificity factor 6 (173, 174) (for a recent review, see Ref.…”
Section: Allinismentioning
confidence: 99%
“…Notwithstanding the lack of sequence specificity, several reports suggest that integration preferentially occurs in nucleosomal rather than in naked DNA; in particular, hot spots for integration have been identified in portions of DNA bent around nucleosomal cores (Pryciak and Varmus, 1992;Muller and Varmus, 1994;Pruss et al, 1994). Several in vivo studies indicate that DNase I hypersensitive regions, which characterize decondensed chromatin, are favorable sites for retroviral integration (Vijaya et al, 1986;Rohdewohld et al, 1987), while heterochromatic regions are disfavored (Carteau et al, 1998). Recently, broad analyses on integration site selection have indeed revealed that retroviruses preferentially integrate near transcriptionally active genes (Schroder et al, 2002;Wu et al, 2003;Mitchell et al, 2004).…”
Section: Introductionmentioning
confidence: 99%